Evaluasi Kepuasan Pengguna Sistem Informasi E-Konseling Arspira Berbasis Website Menggunakan Metode TAM - Muhammad Rizqy; Novan Junaedi; Fajar Mukti Hidayat; Ignatius Wiseto Prasetyo Agung (JURNAL REKAYASA INFORMASI, 2021)
Juvenile delinquency is one of the obstacles for students in self-development and the learning process. Schools have a responsibility to help students overcome this, one of which is by providing guidance and counseling services. The development of information and communication technology can be used for the implementation of online counseling. Arspira's E-Counseling Information System is a website-based information system that can be used for online counseling with various features in it. This study aims to determine the results of the evaluation of user satisfaction using the TAM (Technology Acceptance Model) method, by distributing questionnaires to 41 respondents. The questionnaire data was then analyzed by several tests, namely the research instrument test, the respondent's level of achievement test (TCR), and hypothesis testing. The results show that the variable of computer self-efficacy affects the variable of perceived usefulness by 42.0%, the variable of computer self-efficacy affects the variable of perceived ease of use by 60.9%, the variable of perceived ease of use affects the variable of perceived usefulness by 64.5%, the variable of perceived ease of use affects the variable of attitude towards using by 53.2%, and the variable of perceived usefulness affects the variable of attitude towards using by 72.0%.